Extraction of continuous fiber from mengkuang leaves: The influence of process parameters during alkaline treatment - Hamizol, M.S. (EDP Sciences, 2014)
Currently, natural cellulose fiber composite is a promising prospect in the composite world. However, achieving uniform strength in natural fiber composite is a challenge due to limited fiber length and its random orientation in the composite. Thus, the focus of this paper was to obtain a continuous cellulose fiber from mengkuang leaves using chemical extraction process. The chemical extraction involved alkaline treatment of the mengkuang leave followed by bleaching. This paper focused on extraction using sodium hydroxide (NaOH) and its process parameters. The process parameters of the extraction were varied in terms of concentration of NaOH solution and also the soaking time. The texture and structure of the chemically purified continuous cellulose fiber were observed by visual inspection. Detailed microstructural analysis was carried out using Field Emission Scanning Electron Microscopy (FESEM) while chemical composition analysis in term of cellulose percentage was conducted using Technical Association of the Pulp and Paper Industry (TAPPI); TAPPI T203. Preliminary results showed that increment in cellulose percentage when the concentration of NaOH and soaking time were increased. Â© 2014 Owned by the authors, published by EDP Sciences.